Long term changes in augmentation, potentiation, and depression of transmitter release as a function of repeated synaptic activity at the frog neuromuscular junction. - Magleby, K L (1976)
1. End-plate potentials (e.p.p.s) were recorded from frog neuromuscular junctions under conditions of low quantal content to study the long-term effects of repeated synaptic activity on transmitter release. 2. The nerve terminal was presented with 30-100 successive conditioning-testing trials applied once every 7-10 min over a 4-16 hr perod. Each conditioning-testing trial consisted of a 200-600 impulse conditioning train followed by a series of testing impulses. The magnitudes and time constants of decay of augmentation and potentiation following each successive conditioning train were determined by measuring the e.p.p. amplitudes resulting from the testing impulses. 3. The magnitude of augmentation immediately following the conditioning trains increased an average of 3-4 times (range 1-20) with sucessive trials. 4. As the magnitude of augmentation increased with successive trials the decay of augmentation deviated from a simple exponential, decaying faster immediately after the conditioning train. This faster decay led to a 20% decrease with successive trials in estimates of the time constant obtained from the first 10 or 20 sec of the decay of augmentation. The deviation of the decay of augmentation from a simple exponential could be accounted for if augmentation is related to the 4th power of some substance which decays with a simple exponential time course. Some alternative explantations for the non-exponential decay of augmentation are also discussed. 5. The magnitude of potentiation increased or decreased about 25% with successive trials. 6. The time constant characterizing the decay of potentiation inceased an average of 1-5 times (range 0-8-5 times) with successive trials. 7. The increase in the magnitude of augmentation with successive trials was accompanied by a similar increase in the magnitude of the e.p.p. amplitudes during the conditioning trains, suggesting that augmentation develops during the conditioning train. In some preparatons augmentation appeared to be the major factor acting to increase e.p.p. amplitudes during the conditioning train, having a greater effect than facilitation or potentiation. 8. If a sufficiently large number of successive trials were applied, a depression of e.p.p. amplitudes developed during the conditioning trains and estimates of the magnitude of potentiation following the depressed conditioning trains were reduced...